2016
DOI: 10.1177/0033294115626633
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Interventions for Children with Attention Deficit/Hyperactivity Disorder

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most prevalent neurodevelopmental disorders and is characterized by core symptoms of inattention, impulsivity, and hyperactivity. Given the limitations of the existing treatment strategies, it seems necessary to consider the further exploration of alternative treatment approaches. In this review, the application and complementary use of animal-assisted interventions to the treatment of ADHD were discussed. Several mechanisms including calming, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 139 publications
2
20
0
1
Order By: Relevance
“…As semi-experimental study, the possible effect on the results by the residential treatment itself has to be taken into account. Nevertheless, the results obtained seem to follow the line of other studies that denote the usefulness of AAT with minors [48], substance abuse disorders [46,49], ADHD [39], neuro-rehabilitation [47] and ASD [41]. We did not register past dog ownership; it should be considered in future studies as a covariant.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As semi-experimental study, the possible effect on the results by the residential treatment itself has to be taken into account. Nevertheless, the results obtained seem to follow the line of other studies that denote the usefulness of AAT with minors [48], substance abuse disorders [46,49], ADHD [39], neuro-rehabilitation [47] and ASD [41]. We did not register past dog ownership; it should be considered in future studies as a covariant.…”
Section: Discussionsupporting
confidence: 76%
“…From the data obtained, and taking into account other studies [38], it can be concluded that the implementation of AAT resulted in an encouraging improvement in impulsiveness, which is linked to improvement of psychopathology and, specifically, substance abuse disorders themselves. The decrease in impulsiveness in patients reflects the results obtained in research derived from other applications of AAT, such as studies in attention deficit hyperactivity disorders (ADHD), where AAT is applied in a complementary way, obtaining a positive reduction in symptoms and impulsiveness [39,40]. Regarding the improvement in life skills obtained after the implementation of AAT in patients with dual pathology, other studies have demonstrated similar results.…”
Section: Discussionsupporting
confidence: 73%
“…It may give rise to the same feeling to discover the moose droppings lying on the path where we are The fact that farm animals can have positive effects on especially unfocused and loud children who have difficulties sitting still and have problems with concentration ability is also described in other studies [21,22]. In a review on the effect of animal-assisted interventions on children with ADHD, it is concluded that animals have positive effects on several core symptoms [61].…”
Section: Encounters With the Wild Animalsmentioning
confidence: 89%
“…Systematic reviews of the literature have been conducted to examine the impact of AAI on the health and well-being of children and adolescents [32][33][34][35], and despite the positive results obtained by different authors; criticisms persist with regard to the methodology used and the shortage of protocols. In our study the whole intervention was planned in advance and strict animal welfare and zoonosis prevention protocols were followed.…”
Section: Discussionmentioning
confidence: 99%